Contemporary methods of search for hidden corpses - Trzciński, Maciej (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
Problems associated with searching for missing people are of complex nature. Police statistics clearly show that the number of people reported missing is increasing (in 2014 it exceeded 20,000 people). The etiological factors of the missing person are very diverse in nature and are not always associated with criminal activities. Human trafficking, kidnapping for a ransom and fights between criminal groups undoubtedly generate difficulty in specifying a group of people who are missing. We can also add victims of planned or accidental homicide, suicide, victims of accidents to the group of missing people. The aim of this article is the analysis of methods of searching for hidden corpses, both in urban areas and an open terrain, applied in criminalistics and forensic archaeology.